Rhizobacterial switching towards climate smart agroecosystems - Kaushal, M.; Kaushal, R. (ALOKI Ltd, 2018)
Climate smart agriculture is defined as a systematic and synergetic ingress for transformation and reorientation of agricultural development under constrained environment with climate risks. Enhanced plant productivity and reduced microbial respiratory C can potentially mitigate the rising of the atmospheric CO2 however we are currently in shortfall of efficient routes to accomplish these objectives. Under future climate scenarios of exalted CO2, rhizosphere microbes may serve important links in mediating plant productivity and soil C/N dynamics with optimization of root-soil interface mechanisms to achieve CSA goals. Study was undertaken to precisely quantify microbial biomass-carbon and microbial activity of rhizosphere region of cauliflower (Brassica oleracea var. botrytis) at two different agro-climatic zones. A native bacterial strain Bacillus pumilus isolated from cauliflower rhizosphere was employed that enhanced plant growth, nutrient uptake with improved soil nutrient status. Microbial biomass carbon (119.8 mg MB-C/ 100 g soil) was the highest with the application of Bacillus pumilus and 75% NP fertilizers at both locations. Moreover, the microbial activity was found to be the highest (0.18 mg CO2/ g soil) with the same consortium up to 48 h and then followed a sudden decreasing trend. The results clearly suggest that Bacillus pumilus strains as bio-inoculants can be successfully employed for maintaining soil health being useful in context of climate smart agriculture goals.